2018
DOI: 10.1002/pen.24853
|View full text |Cite
|
Sign up to set email alerts
|

Residual strength and damage mechanisms of laminated carbon fiber reinforced polymer under thermal environments and laser irradiations

Abstract: It is interesting to compare the residual strength of laminated carbon fiber reinforced polymer under thermal environments with finite heating rate, and laser irradiation with rapid heating rate. In these two conditions, heating rates are varied in two orders of magnitude, and thermally-induced damage mechanisms are quite different, which may influence the performance of residual strength. Systematic experiments are performed to obtain the tensile failure behavior of laminated carbon fiber reinforced epoxy com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…e service environment of the FMLs varies a lot in many industries; researchers need to highly restore the service conditions in order to obtain more accurate experimental results. For example, after exposure to ultraviolet or humid air, the chemical composition of the surface of the material may change, thereby greatly reducing the life of the material [14,[130][131][132]. erefore, it is suggested that the influence of environmental factors on FMLs in future research work should be studied.…”
Section: Development Trend Of Fmlsmentioning
confidence: 99%
“…e service environment of the FMLs varies a lot in many industries; researchers need to highly restore the service conditions in order to obtain more accurate experimental results. For example, after exposure to ultraviolet or humid air, the chemical composition of the surface of the material may change, thereby greatly reducing the life of the material [14,[130][131][132]. erefore, it is suggested that the influence of environmental factors on FMLs in future research work should be studied.…”
Section: Development Trend Of Fmlsmentioning
confidence: 99%
“…On the other hand, it is well known that glass fibers (GFs) and carbon fibers are widely used in reinforcing polymers due to their superior mechanical properties, good processability, low manufacturing costs, and so on . Especially for thermoplastics, reinforcement with fibers is a highly attractive approach because the resulting composites can be readily produced in large‐scale using highly efficient commercial process such as extrusion compounding and injection molding .…”
Section: Introductionmentioning
confidence: 99%